Pengaruh Kepercayaan Dan Kemudahan Terhadap Keputusan Pembelian Secara Online Di TiktokShop Pada Mahasiswa UHN Medan - Pandiangan, Meri Mesia; Sihombing, Natalia E.; Degodona, L. Primawati (Research and Community Service UNIVERSITAS KALBIS, 2025)
This research aims to analyze the influence of trust and convenience on online purchasing decisions on the Tiktok Shop buying and selling site among students at HKBP Nommensen University, Medan. This research uses quantitative research methods with data collection techniques through questionnaires. The research results show that the trust variable has a t-value of 5,600. The calculated t-value is smaller than the t-table value (5,600<t-table) also indicates that the hypothesis H0 is accepted. The convenience variable has a t-count value of 8.236 with a probability level (sig) of 0.000. Because this value is smaller than the significance level of 0.05, the t-count value which is greater than the t-table shows that the H1 hypothesis is accepted. The purchase decision F-calculated value of 41.233 is much greater than the F-table of 3.09, so H1 is accepted and H0 is rejected. The coefficient of determination of 0.453 indicates that 45.3 variations in purchasing decisions can be explained by the trust and convenience variables, the remaining 54.7% is explained by other factors not included in this research model.